Pelanggaran Hak Cipta Musik Berbentuk Cover Song di Media Sosial - Uyan Wiryadi (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
The purpose of this study: 1) To find out copyright violations in the field of music in the form of a cover song by recording through social media connected with Law Number 28 of 2014 concerning Copyright. 2) To find out the factors that influence copyright violations in the music field in the form of cover songs by recording through social media. The writing of this thesis uses a statute approach, by reviewing amendments to Law Number 28 of 2014 concerning Copyright and its implications for copyright and its implementation by state institutions and the Republic of Indonesia Law No. 19 of 2016 concerning Amendment of Law Number 11 Year 2008 Regarding Information and Electronic Transactions. Results of research conducted by the author: When someone does a cover song through social media without permission from the creator, both for the purpose not for commercial or commercial purposes, it is an infringement of copyright. Factors that influence the occurrence of violations of copyright in Indonesia include: 1) Weak law enforcement against violators. 2) Works on the internet can easily be duplicated and disseminated globally in a short period of time and in large quantities. 3) There is no limit on the place of the offender because a domain name or website can be accessed by anyone globally. 4) Procedures for events between countries in dealing with violations of copyright on the internet, such as to determine who the perpetrators are and when they occur and determine the jurisdiction of violations still vary.